Epididymitis in mice experimentally infected with Trypanosoma equiperdum: a histopathological and immunohistochemical study. (February 2023) - Tanaka, Yusuke; Suganuma, Keisuke; Watanabe, Kenichi; Kobayashi, Yoshiyasu
ABSTRACT: Trypanosoma equiperdum is a causative agent of dourine in equids and is transmitted from stallions to mares by coitus. Dourine-affected stallions develop orchitis and epididymitis, and these lesions are considered to be responsible for the sexual transmission of T. equiperdum during coitus. However, the parasitic site of trypanosomes in the reproductive organs and the mechanisms underlying transmission have not yet been elucidated histopathologically. We examined the reproductive organs of male mice infected with T. equiperdum histopathologically and identified severe epididymitis with sperm granulomas. Many trypanosomes were detected in the epididymal interstitium and a few were seen within tubular lumen. Interstitial inflammatory cells mainly consisted of Iba1-, iNOS- and CD204-positive cells with a few CD3-, FOXP3- or PAX5-positive cells. There was diffuse immunolabelling of tumour necrosis factor-α (TNF-α) within these inflammatory foci. While caspase-3-positive epithelial cells in the epididymis were not observed in control mice, they were detected multifocally in infected mice and were frequently associated with loss of immunolabelling of zonula occludens-1 (ZO-1), a major protein that forms tight junctions between epididymal epithelial cells. Anti-laminin immunofluorescence revealed an indistinct basement membrane of the epididymal duct. These results suggest that trypanosomes in the epididymal interstitium induce the infiltration of TNF-α-secreting macrophages. Secreted TNF-α may impair the tight junctions of the epididymal duct by inducing apoptosis and downregulating ZO-1 expression.